Competitiveness and macroeconomic impacts of reduced wait times at U.S. land freight border crossings. (August 2015) - Avetisyan, Misak; Heatwole, Nathaniel; Rose, Adam; Roberts, Bryan
Highlights: Economic impacts of reducing delays at 12 major land freight border crossings. Sophisticated macroeconomic modeling applied to extensive U.S. CBP data. Advance of GTAP modeling for exogenous transport cost change and modal substitution. Adding one staff member at each crossing increases U.S. GDP by 350 thousand. Macroeconomic impacts also positive on Mexico and Canada indicating a "win–win". Abstract: We analyze the macroeconomic and trade impacts of reducing wait times by adding one customs officer at each of the twelve major land freight crossings of the U.S. The change in wait time stemming from staffing changes is first estimated on the basis of primary data and then translated into changes in freight costs through a logistical model. The transportation cost changes are then fed into a multi-country computable general equilibrium model. We find that adding one customs officer at each land border crossing would, on average per crossing, generate an increase in U.S. GDP of 350 thousand and 3.58 additional jobs.